Barriers and facilitators to implementing the Activate injury prevention exercise programme – A qualitative study of schoolboy rugby coaches. Issue 6 (December 2022) - Barden, Craig; Watkins, Ross; Stokes, Keith A; McKay, Carly D
The rugby-specific Activate injury prevention exercise programme was deemed efficacious in a randomised controlled trial and subsequently disseminated nationwide by the Rugby Football Union (English rugby union governing body) in 2017. However, no assessment has been made of the factors influencing Activate implementation in an applied setting. Consequently, this study sought to assess the barriers and facilitators to coaches implementing Activate in English schoolboy rugby. This qualitative study adopted a framework approach, using four a-priori themes influencing injury prevention implementation: awareness, motivational determinants, volitional determinants and socio-environmental factors. A purposive sample of schoolboy rugby coaches were recruited from schools nationwide, participating in semi-structured, one-on-one interviews (n = 10). Transcripts were thematically coded. Participants had positive perceptions towards Activate, although only six adopted the programme. Participants reported that players were generally unaware of the programme, with some suggesting this was not an issue as coaches made the decision to adopt Activate . Participants focused heavily upon the use of resources to develop coaches' awareness, knowledge and confidence. No participant implemented Activate as initially designed, influenced by time and engagement, instead incorporating it within training drills rather than as a block at the beginning of the session. Participants adapted the programme to make it suitable for multiple sports. Some participants reported asking players to deliver Activate, despite their lack of awareness, raising concerns around implementation. Participants heavily adapted Activate delivery to suit their contexts. How this affects the effectiveness of Activate to reduce injury risk is unknown and should be investigated. Player-specific dissemination strategies should be considered if these individuals act as delivery-agents.